2006
DOI: 10.1111/j.1745-4557.2006.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE EFFECTS OF LACTIC ACID, NISIN, COATING COMBINED AND ALONE APPLICATIONS ON SOME POSTMORTEM QUALITY CRITERIA OF REFRIGERATED SARDINA PILCHARDUS

Abstract: Fish meat is highly prone to microbiological contamination from hunting and slaughtering stages to the transportation and kitchen, especially by Pseudomonas spp. In this study, effects of nisin (0.04 g/L/kg at pH 5.2), lactic acid (5% at pH 2.9) and their combinations were studied on coated (where vegetable oil, beeswax and distilled water mixture with pH 7.2 was used as the main coating material) and noncoated fish specimens on inhibition of Pseudomonas and mesophilic aerobic bacteria (MAB) at refrigeration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…However, this effect has been reported to be specially important in the case of LA, as being recognised as effective in suppressing Gram-negative bacteria activity, which are known to be the most important fish spoiler group. Thus, previous research reports on an extension of shelf life in fish fillets [14,15] and coated fish [16] by employing LA as a previous treatment.…”
Section: Lipid Hydrolysis Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this effect has been reported to be specially important in the case of LA, as being recognised as effective in suppressing Gram-negative bacteria activity, which are known to be the most important fish spoiler group. Thus, previous research reports on an extension of shelf life in fish fillets [14,15] and coated fish [16] by employing LA as a previous treatment.…”
Section: Lipid Hydrolysis Developmentmentioning
confidence: 96%
“…Thus, ascorbic and citric acids (AA and CA, respectively) and their salts are widely known for their role as chelators, acidulants in biological systems and synergists of primary antioxidants, so that a profitable effect on fish oil and emulsions [7,8], minced fish [9,10], fish fillets [11,12] and whole fish [13] have been observed. Further, lactic acid (LA) has been reported to be effective in suppressing Gram-negative bacteria, which are known to be the most important fish spoiler group; thus, LA pre-treatment has shown to be effective in preserving and extending shelf-life in fish fillets [14,15] and coated fish [16].…”
Section: Introductionmentioning
confidence: 99%
“…In samples with 4% supernatant and live cells with concentration of 6log CFUg -1 , the number of psychrophilic bacteria on 15th day were 5.36±0.09, 4.25±0.06 logCFUg -1 , respectively ( Figure 1) that were less than human consumption limit. [21][22][23] Although, adding 2% supernatant to rainbow trout fillet was effective to reduce psychrophilic bacteria, but adding 4% supernatant had better results that showed the advantage of adding 4% supernatant in immersion method Also, the results showed that using live bacteria and 4% supernatant induced significant difference (p<0.05). However, the use of supernatant had a relative advantage due to lower psychrophilic bacteria density during rainbow trout fillet storage compared to live cells (Figures 1 and 2) (p<0.05).…”
Section: Discussionmentioning
confidence: 73%
“…Treatment with lactic acid has also been reported to be effective for extending the shelf lives of fish fillets (Kim, Hearnsberger, & Eun, 1995;Metin, Erkan, Varlik, & Aran, 2001) and coated fish (Gogus, Bozoglu, & Yurdugul, 2006). Interestingly, the effectiveness of inhibiting the growth of Gram-negative bacteria, which are responsible of fish spoilage, has also been reported (Alakomi et al, 2000).…”
Section: Introductionmentioning
confidence: 96%